Tewkesbury Abbey
Shaped stone for building this great abbey church, the second largest parish church in England was brought by the sea from Caen in Normandy. Its circular columns and arches are typical, but the roof-which was later vaulted in the fifteenth century-replaced an earlier timber structure. The rapid changeover from the construction of small buildings by local craftsmen out of local materials, to a prototype industrial system was another of the major products of the Norman Conquest.